H-shaped Talon Cusp in the Anterior Maxilla: A Diagnostic Dilemma - Nawadir Hamoud Alanazi; Josnavinutha Yadiki (Journal of Clinical and Diagnostic Research, 2024)
Dental anomalies are clinically evident abnormalities that cause a variety of dental problems. Depending on the tooth location, dens evaginatus indicates a posterior tooth abnormality, while talon cusp explains an anterior tooth anomaly. Identifying the problem and initiating treatment requires careful observation and proper investigations. Here, the authors present the case of a nine-year-old female child who had an H-shaped talon cusp or barrel-shaped bilateral maxillary lateral incisors in the form of premolars. The report includes clinical and radiographic interpretation. Associated problems and various treatment options are also explained. Although dental anomalies affecting the teeth are relatively common, the presentation of barrel-shaped or premolar-shaped bilateral maxillary lateral incisors is uncommon. Knowledge about the prevalence and distribution of such anomalies would aid various dental experts in early identification and recognition of dental malformations, as well as in complete treatment planning.